2016
DOI: 10.1038/tp.2016.102
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy and structural neuroplasticity in neocortical, limbic and paralimbic cortex

Abstract: Electroconvulsive therapy (ECT) is a highly effective and rapidly acting treatment for severe depression. To understand the biological bases of therapeutic response, we examined variations in cortical thickness from magnetic resonance imaging (MRI) data in 29 patients scanned at three time points during an ECT treatment index series and in 29 controls at two time points. Changes in thickness across time and with symptom improvement were evaluated at high spatial resolution across the cortex and within discrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 82 publications
7
86
2
1
Order By: Relevance
“…However, several of these neuroplastic changes do not significantly relate to changes of clinical response. Specifically, in our prior studies, changes in hippocampal and ACC morphometry and functional connectivity between the dorsal ACC, mediodorsal thalamus, hippocampus, right anterior temporal, medial parietal, and posterior cingulate cortex show moderate relationships with ECT symptom improvements (51, 52, 54). It is thus plausible that changes in particular structural and functional networks may relate to changes in cognitive function occurring with ECT that are at least partially independent of changes in network activity relating to clinical outcome.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, several of these neuroplastic changes do not significantly relate to changes of clinical response. Specifically, in our prior studies, changes in hippocampal and ACC morphometry and functional connectivity between the dorsal ACC, mediodorsal thalamus, hippocampus, right anterior temporal, medial parietal, and posterior cingulate cortex show moderate relationships with ECT symptom improvements (51, 52, 54). It is thus plausible that changes in particular structural and functional networks may relate to changes in cognitive function occurring with ECT that are at least partially independent of changes in network activity relating to clinical outcome.…”
Section: Discussionmentioning
confidence: 76%
“…Other studies have reported ECT-induced normalizing effects in the structure and function of the brain. For example, in an overlapping sample, we have reported ECT-induced neuroplasticity in the hippocampus and amygdala (51), and increased cortical thickness of the bilateral anterior cingulate cortex (ACC), inferior and superior temporal, parahippocampal, entorhinal and fusiform cortex and in distributed prefrontal areas over the course of ECT (52). We have also shown significant increases of fractional anisotropy (FA) indicating improved structural connectivity in dorsal fronto-limbic circuits (53).…”
Section: Discussionmentioning
confidence: 99%
“…EMBARC provides a unique opportunity to examine pretreatment and short-term alterations in brain structure occurring within the first week of SSRI and placebo treatment. Cortical thickness alterations in the 1-week interval used in this study have been shown to be detectable via 3T structural MRI, for example, in learning new tasks [42] and following electroconvulsive shock therapy [43]. EMBARC's double-blind, randomized, placebocontrolled structure provides a basis for understanding whether potential structural treatment response markers are specific to the SSRI, sertraline.…”
Section: Discussionmentioning
confidence: 90%
“…Reduced depressive symptom severity after cognitive training for TBI was related to increased cortical thickness over time only within the TBI‐plus‐depressive symptoms group (Figure ). The depression literature has reported increases in cortical thickness following treatment for depression (van Eijndhoven et al, ; Phillips, Batten, Tremblay, Aldosary, & Blier, ; Pirnia et al, ). Our study extends this line of research by demonstrating intervention‐induced neuroplasticity in TBI with comorbid depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%